Vimentin Intermediate Filaments as Potential Target for Cancer Treatment - Strouhalova, Katerina; Přechová, Magdalena; Gandalovičová, Aneta; Brábek, Jan; Gregor, Martin; Rosel, Daniel (Cancers, 2020)
Intermediate filaments constitute the third component of the cellular skeleton. Unlike actin and microtubule cytoskeletons, the intermediate filaments are composed of a wide variety of structurally related proteins showing distinct expression patterns in tissues and cell types. Changes in the expression patterns of intermediate filaments are often associated with cancer progression; in particular with phenotypes leading to increased cellular migration and invasion. In this review we will describe the role of vimentin intermediate filaments in cancer cell migration, cell adhesion structures, and metastasis formation. The potential for targeting vimentin in cancer treatment and the development of drugs targeting vimentin will be reviewed.
Keywords: invasion; cancer treatment; cell adhesion; mechanotransduction; cancer drugs; vimentin; mesenchymal; amoeboid; EMT